(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A significant role is played by financial system in economic transformation of a nation. It acts asan intermediary between borrower and lender, provide various saving opportunity with different riskreturncharacteristics. It bridges that gap between the present and future and mobilizes the savings intoproductive channels of investment. Financial system comprises of financial institutions, stock market,pension fund, insurance sector etc. Developing countries give more importance to expansion of financialsector and its coverage in an effort to reduce poverty. For country’s prosperity, its growth is at mostimportant. Effective mobilization of savings, smooth payment system and efficient distribution ofresources are key drivers for this sector. Financial system helps the financial market to expand over aperiod of time. It facilitates effective distribution of resources among productive and socially desirablepurpose in an economical manner. Financial institutions such as banks are an essential element for acountry’s financial system. They play a pivotal role in progress of rural provinces of Indian economy.Finance is the key element in achieving the long-term prosperity of a country. It is an importantrequirement to meet the credit needs of every sector i.e. agriculture, manufacturing, trade and otherservices for smooth functioning of their day to day operations and for growth as well.